Exploring the Mediating Role of Attitude between Serendipity and Trust in Seller toward Online Purchase - Reni Suci Wahyuni; Ahmad Syarif Mutsanna; Dani Rizana (Value Added : Majalah Ekonomi dan Bisnis, 2026)
This study investigates the effects of serendipity and trust in seller on online purchase intention, with attitude functioning as a mediating variable among Shopee Live users in Central Java, Indonesia. A quantitative survey approach was employed, involving 150 respondents, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both serendipity and trust in seller exert positive and significant effects on attitude and online purchase intention, both directly and indirectly through attitude. These results indicate that affective experiences and cognitive trust operate synergistically in shaping consumers’ online purchasing intentions. Theoretically, this research extends the application of the Theory of Reasoned Action and the Stimulus–Organism–Response (S-O-R) framework within the context of live commerce. Practically, it offers strategic insights for e-commerce practitioners to enhance interactive experiences and strengthen consumer trust in digital marketplaces.